Trigonotis doormanensis, a new name for Trigonotis vestita P.Royen (Boraginaceae) - Xue, Bine (Phytotaxa, 2017)
Trigonotis doormanensis B.Xue is proposed to replace Trigonotis vestita Royen, a later homonym of Trigonotis vestita (Hemsley) Johnston.